Efficacy of levonorgestrel intrauterine system (LNG-IUS) for abnormal uterine bleeding and contraception - Tariq, Nabia; Ayub, Rukhsana; Jaffery, Tara; Rahim, Faisal; Naseem, Fauzia; Kamal, Maryam (Journal of the College of Physicians and Surgeons--Pakistan, 2011)
To find out clinical response, side effects and patients' acceptability of levonorgestrel-releasing intrauterine system (LNG-IUS). Observational study. Gynaecology Department of Shifa International Hospital, Islamabad, from June 2005 to May 2008. Adult women were enrolled in the study. In group-A, 57 married women were enrolled presented with abnormal uterine bleeding while in group-B, 16 married women attended for contraception. All women in group-A had thyroid stimulating hormone, pelvic ultrasound and outpatient endometrial biopsy. Detailed counselling was done before insertion. Outcome variables were improvement in bleeding pattern, safety profile, spontaneous expulsion rate and continuation at the end of one year. In group-A (abnormal bleeding) menstrual cycle became normal in 40.4% women in the first 3 months. At the end of one year, 50.9% women experienced normal cycle, 8.8% were oligomenorrhic and 12.3% were amenorrhic. In group-B (contraceptive group) all women started with normal cycles. At the end of 3 months 42% complained of vaginal spotting which reduced to 10% at the end of one year. Menstrual pattern at the end of one year showed normal cycles in 52%, oligomenorrhea in 19% and amenorrhea in 10% women. Vaginal spotting was experienced by 42% women at 3 months as main complaint which reduced to 10% at the end of one year, however, 7% women requested for removal of device at one year. LNG-IUS is an effective and acceptable treatment for abnormal uterine bleeding as well as for contraception. Vaginal spotting was the most frequent side effect experienced by both groups.